Towards a better monitoring of seed ageing under ex situ seed conservation. (1st July 2015) - Fu, Yong-Bi; Ahmed, Zaheer; Diederichsen, Axel
Abstract : Monitoring seed viability in a large volume of ex situ seed germplasm conserved in genebanks is a challenging task for germplasm conservation. This review summarizes the recent development of tools for assessing seed ageing, and highlights seed biology research with ageing signals that hold potential for use in seed deterioration assessments Abstract : Long-term conservation of 7.4 million ex situ seed accessions held in agricultural genebanks and botanic gardens worldwide is a challenging mission for human food security and ecosystem services. Recent advances in seed biology and genomics may have opened new opportunities for effective management of seed germplasm under long-term storage. Here, we review the current development of tools for assessing seed ageing and research advances in seed biology and genomics, with a focus on exploring their potential as better tools for monitoring of seed ageing. Seed ageing is found to be associated with the changes reflected in reactive oxygen species and mitochondria-triggered programmed cell deaths, expression of antioxidative genes and DNA and protein repair genes, chromosome telomere lengths, epigenetic regulation of related genes (microRNA and methylation) and altered organelle and nuclear genomes. Among these changes, the signals from mitochondrial and nuclear genomes may show the most promise for use in the development of tools to predict seed ageing. Non-destructive and non-invasive analyses of stored seeds through calorimetry or imaging techniques are also promising. It is clear that research into developing advanced tools for monitoring seed ageing to supplement traditional germination tests will be fruitful for effective conservation of ex situ seed germplasm.